Transcriptomic profiling of platelet senescence and platelet extracellular vesicles - Pienimaeki Roemer, Annika (2017)
BACKGROUND: Platelets (PLTs) are derived from megakaryocytes during PLT shedding. Senescent or activated PLTs are expanded in vascular and neurological diseases and release PLT extracellular vesicles (PL-EVs). A systematic analysis of regular messenger RNA (mRNA) and small RNA composition in PLTs and PL-EVs during in vitro PLT senescence has not yet been published. STUDY DESIGN AND METHODS: We isolated PLTs, total PL-EVs, and PL-EV subsets on Days 0 and 5 from human stored donor platelet concentrates. Isolated mRNA species and microRNA (miRNA) species were analyzed by microarrays and deep sequencing. Correlation of mRNA and miRNA species (miR) and miRNA target analyses were performed using bioinformatics. RESULTS: During in vitro PLT senescence, residual PLT mRNA species were decreased and partially converted to miRNA species. Residual mRNAs included encoded genes relevant for atherosclerosis, inflammation (matrix metallopeptidase 14 [MMP-14], granulin [GRN], angiopoietin like 2 [ANGPTL2]), and neurotransmission (dopamine receptor 2 [DRD2], γ-aminobutyric acid type A receptor ρ3 [GABRR3]). Compared with senescent PLTs, PL-EVs have up-regulated their miRNA species involved in “diabesity” and in vascular and metabolic disease (miR-144-3p, miR-486-5p, miR-142-5p, miR-451a, miR-25-3p, miR-145-5p, and let-7f-5p). The 100 highest expressed PL-EV miRNA species determined by microarrays were compared with the 100 highest expressed PL-EV miRNA species detected by deep sequencing. This approach resulted in 66 overlaps. The regulated miRNAs (assessed by both methods) were related to neurological disorders, including targets for Alzheimer's disease (e.g., β-site amyloid precursor protein APP-cleaving enzyme 1 [BACE1], translocase of outer mitochondrial membrane 40 homolog [TOMM40], neuron navigator 3 [NAV3]). CONCLUSION: During in vitro senescence, PLTs degrade large RNA species. Concomitantly, they up-regulate a distinct set of known small RNA species involved in atherosclerosis, inflammation, and neurodegeneration. PL-EVs enrich miRNA species, likely supporting the role of PLTs and PL-EVs in vascular homeostasis and as carriers of neurodegenerative disease-related miRNA cargo.